Characterization and Identification of Caffeine-Degrading Bacteria KAJ 36 - Sattya Arimurti; Reza Billa Afifuddin; Siswanto Siswanto; Kahar Muzakhar (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2020)
Caffeine could be utilized by caffeine-degrading bacteria as a source of carbon and nitrogen. These bacteria have the potential as an agent of decaffeinating coffee. The objective of this research was to characterize and identify the caffeinedegrading bacteria KAJ 36 that was isolated from the pulp waste of Coffea arabica. The isolate-characterization was performed based on its growth and caffeine degradation activity.in a medium M9 added with 10 g/L caffeine for 7 days. The isolate identification was conducted using 16S rRNA sequence analysis and biochemical analysis. The result indicated that caffein-degrading bacteria were able to grow and degrade the caffein up to 86% activity on M9 medium added 10 g/L caffeine for 7 days incubation. Based on 16S rRNA, the isolated KAJ 36 had sequences of 99% homology with Pseudomonas monteilii. Biochemical analysis showed that this isolation on the specific medium was a gram-negative, oxidative, positive enzymatic activity (oxidase, catalase, urease) and reduce nitrate. Our results showed that the isolated KAJ 36 was capable of producing fluorescent pigment. This bacterium was unable to produce indole or utilize sucrose and lactose. Based on the cultural characteristics, we found that the isolated KAJ 36 could be grown in a medium with pH 5, 7, and 9, and in the environment with up to 37oC. This evidence suggested that P. monteilii KAJ 36 can be used as a potential degradation agent of caffeine and recommend for future research in the bacterial based on the degradation of caffeine-contained coffee.